2015
DOI: 10.7861/clinmedicine.15-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Omitted medications: a continuing problem

Abstract: Failure to provide prescribed medicines to inpatients has the potential to cause signifi cant patient harm, to delay the resolution of the pathology and to increase the length of hospital stay. We measured the frequency at which medications were omitted in the non-admitting medical wards of a district general hospital, using two point-prevalence studies spaced one month apart. The results showed that the omission of prescribed medications remains a problem throughout the hospital stay of the patient. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 7 publications
7
28
0
Order By: Relevance
“…However, Shandiva et al . () studied charts that were completed for more than one medication administration round, magnifying the risk of omission with every round completed, in contrast with only one medication round observed in this study, thus explaining the discrepancy. Shandiva et al .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…However, Shandiva et al . () studied charts that were completed for more than one medication administration round, magnifying the risk of omission with every round completed, in contrast with only one medication round observed in this study, thus explaining the discrepancy. Shandiva et al .…”
Section: Discussionmentioning
confidence: 74%
“…The 41% of errors represented by omissions were comparable to the 36% mentioned by Bowns and Gill (), although Shandiva et al . () found that up to 73% of patients were affected by omissions. However, Shandiva et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed a high prevalence of patient refusal; accounting for over a third of dose omissions. Various smaller studies have also reported that the most common reason for medication omission is patient refusal, accounting for up to 45% of dose omissions . Whilst it is important for patients to retain autonomy in their health care, particularly during hospitalization, it is also important to determine the reason for dose refusal.…”
Section: Discussionmentioning
confidence: 99%